Differences in Future Anxiety Levels in Fresh Graduates Based on Family Background - Khairul Amri; M. Fahli Zatrahadi; Miftahuddin Miftahuddin; Reizki Maharani (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
The move from higher education into the labour market is a demanding passage, and fresh graduates often enter it carrying considerable worry about what lies ahead. Guided by the family stress model, this study asked whether future anxiety differs by parental income, an indicator of family socioeconomic status, among fresh graduates in Pekanbaru, Indonesia, a city where open unemployment among university graduates remains a live concern. A causal-comparative design was used. Forty-five fresh graduates, defined as having completed their degree within the preceding two years and residing in Pekanbaru, were recruited through purposive sampling against fixed inclusion criteria. Future anxiety was measured with a 21-item instrument adapted from the Indonesian Future Anxiety Scale (Ruddin & Nuryanti, 2026), itself a cross-cultural adaptation of Zaleski’s (1996) Future Anxiety Scale, rated from 0 to 6 (Cronbach’s α = .902). Parental income was grouped into low, middle, and high categories and compared using one-way ANOVA with η² and ω² effect sizes, a confirmatory Kruskal Wallis test, and Spearman correlations; a sensitivity power analysis accompanied the comparison. Future anxiety did not differ significantly across income groups, F(2, 42) = 1.894, p = .163, η² = .083 (95% CI [.005, .380]), ω² = .038; Kruskal–Wallis H(2) = 1.981, p = .371. With 45 participants the achieved power was only .40, and detecting an effect of the observed size at .80 power would require roughly 110 participants. The absence of a significant difference should therefore be read as absence of evidence rather than evidence of absence. The study offers early local evidence on graduate well-being and argues for career counselling that is inclusive across income strata and informed by theory rather than by economic assumptions alone.